(NpOLIKONDENSACIONNYE PROCESSY I POLIMERY (B:s (NmEVWUZOWSKIJ TEMATI^ESKIJ SBORNIK NAU^NYH TRUDOW (B/s - (NkOR[AK(B, (NwASILIJ wLADIMIROWI^s; (NkABARDINO(B-(NbALKARSKIJ GOSUDARSTWENNYJ UNIWERSITETs ((NnALX^IK (B:s (Nkbgu(B,s, 1981)
(NbIBLIOGR(B. (NW KONCE ST(B.s
Keywords: (NpOLIKONDENSACIQs; (NpOLIMERYs -- (NsINTEZs